Climate Change and the Relocation of Population - Jasmin Gröschl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Do natural disasters trigger intensified international migration? The aim of this paper is to assess the extent to which disasters initiate bilateral migration. To motivate the empirical strategy, I construct a stylized theoretical gravity model of migration that introduces disasters as random shocks. I present estimations that deploy a dataset of bilateral migration available for increments of 10 years from 1960-2010 for a large matrix of countries. Results suggest that disasters are on average positively associated with migration out of affected areas, but negatively for migration into affected countries. In addition, I show that results are primarily caused by disasters related to climate change. Migration to and from non-OECD and particularly middle income countries drive the patterns.
Keywords: F22; O15; Q54; 330